MES vs ∆CoVaR: Empirical evidence from Pakistan - Hasan Hanif; Imran Yousaf; Abdul Waheed; Waseem ullah (Cogent Business & Management, 2021)
The global financial crisis unveiled that inadequate analysis of risk can annihilate the financial system and repercussions can encompass the whole economy. Pakistan is one of the developing economies that has experienced robust growth in the banking sector. This hard earned growth can only be sustained by adequately examining the risk exposure of the financial system. Consistent with this purview, this study attempts to comprehensively analyse for the first time, the systemic importance of financial institutions of Pakistan using ∆CoVaR and MES. Moreover, the study employs System GMM to analyze the bank, sector and country level determinants of systemic risk measures. The findings of the study signify that MES and ∆CoVaR measures identify different institutions as systemically important. Similarly, the influence of variables also changes with change in the systemic measure. The estimation of determinants of systemic risk outline that non-interst income is insignificant when MES is used as measure of systemic risk but the same turns significant for ∆CoVaR. The impact of deposit ratio also changes across the measures of systemic risk. Concentration has positive impact on MES but negatively influences ∆CoVaR. Finally, the impact of bank claims also varies across the measures of systemic risk. The study contributes to the literature by highlighting the complementary nature of systemic risk measures for the first time in a developing economy like Pakistan. The study also identifies important relationships necessary to chalk out micro and macro prudential regulations imperative for the stability of financial system.
Keywords: D62; E58; G01; G28; G32; 650; MES; ∆; CoVaR; DCC; Developing Economy & System GMM